Morphometric evaluation of the slot of aesthetic orthodontic brackets - Jorge Maza-Sánchez; Víctor Marcel Aguilar-Salas (Journal of Oral Research, 2021)
Introduction: Dental malocclusion is a public health problem and orthodontics is the specialty in charge of diagnosing and treating it, aesthetic brackets are an alternative, the costs are varied, which makes its precision doubtful. Objective: Evaluate the measurement and geometry of the slot of three brands of aesthetic brackets and verify their precision. Material and Methods: Twenty-four aesthetic Roth prescription 0.022” slot polycrystalline ceramic brackets were evaluated in three brands: American Orthodontics (United States), Morelli (Brazil) and Class One (China). Eight samples were measured per group in a specialized laboratory certified in measurement and calibration, the measurements of internal and external height were verified, per mesial and distal; and the parallelism of the slot of each bracket. The results were processed with SPSS 22 and tests of variance (ANOVA), Tukey and Student's t were used. Results: The measurements of the brackets' grooves do not correspond to the measurements announced by the manufacturers, these are greater, however, American Orthodontics is within the tolerance range (p<0.01); the slots in the mesio-distal direction and the lingual vestibule are not parallel in Morelli and Class One. Conclusion: The results of this study indicate that the slots of the supports are oversized, their geometry is not precise and varies greatly between brands and prices. The three-dimensional control of the tooth could be compromised.